Analysis of Company Performance Measurement using the Balanced Scorecard Method - Arif Setiawan; Andry Arifian Rachman (Journal of Accounting Auditing and Business, 2020)
This study aims to determine how the performance of the Regional Water Company of Sleman Regency by using the Balanced Scorecard method viewed from a financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. The results of the study show that the performance of the Regional Water Company of Sleman Regency in 2015-2017 can be said to be good, and included in the "healthy" category, with a total performance value of 3,035 in 2015; 3,110 in 2016; and 3,480 in 2017